Escherichia coli O157: detection and quantification in cattle feces by quantitative PCR, conventional PCR, and culture methods - Noll, Lance (Kansas State University, 2015)
Shiga toxin-producing E. coli O157 is a major foodborne pathogen. The organism colonizes the hindgut of cattle and is shed in the feces, which serves as a source of contamination of food. Generally, cattle shed E. coli O157 at low concentrations (≤ 10[superscript]2 CFU/g), but a subset of cattle, known as “super-shedders”, shed high concentrations (>10[superscript]3 CFU/g) and are responsible for increased transmission between animals and subsequent hide and carcass contamination. Therefore, concentration data are an important component of quantitative microbial risk assessment. A four-plex quantitative PCR (mqPCR) targeting rfbE[subscript]O157, stx1, stx2 and eae was developed and validated to detect and quantify E. coli O157 in cattle feces. Additionally, the applicability of the assay to detect E. coli O157 was compared to conventional PCR (cPCR) targeting the same four genes, and a culture method. Specificity of the assay to differentially detect the four genes was confirmed. In cattle feces spiked with pure cultures, detection limits were 2.8 x 10[superscript]4 and 2.8 x 10[superscript]0 CFU/g before and after enrichment, respectively. Detection of E. coli O157 in feedlot cattle fecal samples (n=278) was compared between mqPCR, cPCR, and a culture method. Of the 100 samples that were randomly picked from the 136 mqPCR-positive samples, 35 and 48 tested positive by cPCR and culture method, respectively. Of the 100 samples randomly chosen from the 142 mqPCR-negative samples, all were negative by cPCR, but 21 samples tested positive by the culture method. McNemar’s chi-square tests indicated significant disagreement between the proportions of positive samples detected by the three methods. Applicability of the assay to quantify E. coli O157 was determined with feedlot cattle fecal samples (n=576) and compared to spiral plate method. Fecal samples that were quantifiable for O157 by mqPCR (62/576; 10.8%) were at concentrations of ≥ 10[superscript]4 CFU/g of feces. Only 4.5% (26/576) of samples were positive by spiral plate method, with the majority (17/26; 65.4%) at below 10[superscript]3 CFU/g. In conclusion, the mqPCR assay that targets four genes is a novel and more sensitive method than the cPCR or culture method to detect and quantify E. coli O157 in cattle feces.
Keywords: Shiga toxin; Escherichia coli O157; Real time PCR; Super shedder; Cattle feces; Microbiology (0410)